The role of exercise induced capillarization adaptations in skeletal muscle aging: a systematic review - Ding, Yi; Wan, Qiliang; Kim, Jae Cheol; Liu, Wenduo; Ji, Weiping (Frontiers in Physiology, 2025)
BackgroundSkeletal muscle aging is often accompanied by capillary rarefaction, which limits the effective delivery and distribution of hormones, nutrients, and growth factors within skeletal muscle. Furthermore, exercise is widely regarded as having the potential to improve microcirculation and delay skeletal muscle aging. This review aims to explore exercise-induced improvements in capillarization and related adaptations to mitigate the adverse changes that occur during the aging process of skeletal muscle.MethodsThis systematic review was conducted in accordance with the PRISMA guidelines and registered in the PROSPERO database under the identifier CRD420251055873. Studies involving exercise interventions in older adults were included, with the requirement that at least one original outcome related to skeletal muscle capillarization was reported. Articles were rigorously screened based on the PICOS criteria, and the quality of the included studies was assessed.ResultsStudies have shown that older adults still possess the capacity to improve skeletal muscle capillarization through exercise. Moderate-intensity aerobic exercise not only significantly enhances the level of capillarization but also induces effects that can be maintained even after cessation of training. Capillarization adaptations induced by resistance training exhibit marked inter-individual variability, which is primarily determined by each individual’s baseline level of capillarization, thereby resulting in distinct patterns of adaptation. The studies also revealed that the regulation of capillarization depends on the synergistic action of VEGF and eNOS, and that different types of exercise may elicit adaptations through distinct molecular pathways.ConclusionDuring the aging process, exercise-induced improvements in capillarization can enhance nutrient delivery, metabolic efficiency, and regenerative capacity in skeletal muscle. To some extent, these adaptations help suppress degenerative changes in muscle function and provide a targeted foundation for anti-aging intervention strategies.